The - Ramadhan, Muhammad Rafenza; Kholilah, Kholilah (E-Jurnal Akuntansi, 2024)
The  inventory  valuation  method  has  significant  implications  for financial  statements  and  managerial  decision-making.This  study evaluates  the  influence  of  inventory  intensity,  variability,  current ratio, and leverage on selecting an inventory valuation method with firm  size  as  moderation.The  research  object  includes  all  companies listed on the Indonesia Stock Exchange for 2020-2023. The sample in this study was obtained using the purposive sampling method, with the final samples are 303 companies with a total of 1,212 observation data. The collected data were analyzed using logistic regression and moderation  regression  analysis  for  hypothesis  testing.  The  results show  that  variability,  current  ratio,  and  leverage  have  a  negative effect  on  the  selection  of  inventory  valuation  methods.Meanwhile, inventory   intensity   does   not   affect   the   selection   of   inventory valuation methods. Furthermore, firm size strengthens the influence of  inventory  intensity  and  variability  on  the  selection  of  inventory valuation   methods.  This  study  shows  that  selecting  the  correct inventory   valuation   method   can   be   a   company's   strategy   for optimizing inventory management.